Characteristics of neuropathic pain in patients with diabetes mellitus (Annals of Medical Research, 2021)
Aim: Epidemiological data on the frequency, quantity, and consequences of symptomatic diabetic neuropathy remain poor. We conducted this study to examine the characteristic of neuropathic pain in patients with diabetes mellitus (DM).Materials and Methods: Average daily pain intensity was measured using a 100 mm visual analog scale (VAS). Localization of the pain, position that aggravated pain, frequency of the pain, duration of the pain, pain’s influence on daily living activities were examined.Results: The average patient age was 62.56 years and the number of males was 21 (42%). 29 Patients had only DM and 13 patients had hypertension (HT) plus DM, 4 patients had DM+HT+heart disease. The mean of pain according to VAS was 6.86±2.79. Thirty-two patients defined that the pain affected their daily living activities negatively; 30 patients’ pain localization was lower extremity,12 patients’ was upper and lower extremity; mostly pain was aggravated by standing and 40 patients’ pain frequency was as every day; 24 patients’ pain duration was less than 1 year and 18 patients’ was between 1-5 years.Conclusion: Studies on diabetic neuropathy are important drivers to improve the treatment of these patients. Neuropathic pain is considered to be more serious than other types of pain. So patients diagnosed with DM should be examined for neuropathic pain and the treatment plan should include pain decreasing medication and/or neurosurgical interventions.
Keywords: Diabetes mellitus; neuropathic pain, pain; spinal cord stimulation